Prevalence and factors associated with depressive symptoms among medical students in their first and final year of study - Čanković, Sonja; Mijatović Jovanović, Vesna; Harhaji, Sanja; Šušnjević, Sonja; Ukropina, Snežana; Kvrgić, Svetlana; Čanković, Dušan (Vojnosanitetski pregled, 2023)
Background/Aim. The mental health of medical students worsens during their studies, and research shows that medical students are at high risk for depression. The aim of this study was to evaluate the prevalence of depressive symptoms and to examine the association between various risk factors and depressive symptoms among a sample of first and sixth-year medical students at the University of Novi Sad. Methods. A cross-sectional study was conducted at the Medical Faculty University of Novi Sad, Serbia. The sample consisted of 308 students (213 students in the first year and 95 in the final year of study). The Patient Health Questionnaire (PHQ-9) was used to measure depressive symptoms. Within this instrument, item 9 was used to identify suicidal ideation. Self-esteem was evaluated with the Rosenberg Self-Esteem Scale. Additional questions were focused on self-assessed material status, lifestyle factors, and mental healthcare-seeking. Univariate and multivariate logistic regression analyses were applied. Results. The prevalence of depressive episode among medical students was 16.6%. Almost 9% had thoughts of committing suicide. First-year students with low self-esteem were almost seven times more likely to suffer from moderate to severe depressive symptoms than those with high self-esteem. Students who had used sleeping pills or sedatives without prescription were nearly five times more likely to have a PHQ-9 score ≥10 than those who had not (OR=4.97, 95%CI: 1.83-13.52). Six-year students with poor or average self-assessed social relationships and low self-esteem had a stronger association with a PHQ-9 score ≥10. Conclusion. There is a high prevalence of depressive episode among first and six-year medical students and is associated with low self-esteem in both groups, use of sleeping or sedative pills without a prescription among first-year and poor social health in six-year students. We recommend routine screening for depression in medical students and establishing prevention and intervention programs.